2017
DOI: 10.1017/s0022215117001670
|View full text |Cite
|
Sign up to set email alerts
|

Hearing status in patients with rheumatoid arthritis

Abstract: Higher bone conduction thresholds in some frequencies were detected in rheumatoid arthritis patients that were not clinically significant. Sensorineural hearing loss is significantly more prevalent in refractory rheumatoid arthritis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…Lobo FS with the aim of Distortion product OAEs detected a significant reduced amplitude of OAEs at 2000 Hz bilaterally compared with control subjects ( Lobo et al., 2016 ). However Rahne T and Ahmadzadeh A did not find any decrease in OAE amplitudes evaluated by Distortion product OAEs ( Ahmadzadeh et al., 2017 , Rahne et al., 2017 ).…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 82%
See 2 more Smart Citations
“…Lobo FS with the aim of Distortion product OAEs detected a significant reduced amplitude of OAEs at 2000 Hz bilaterally compared with control subjects ( Lobo et al., 2016 ). However Rahne T and Ahmadzadeh A did not find any decrease in OAE amplitudes evaluated by Distortion product OAEs ( Ahmadzadeh et al., 2017 , Rahne et al., 2017 ).…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 82%
“…Besides, Ahmadzadeh A in a case control study of 42 RA patients compared to the age- and sex-matched healthy individuals demonstrated a significantly higher bone conduction threshold in the patients with RA in low frequencies and in the mean of 500–2000 Hz frequencies. The prevalence of CHL, SNHL and MHL, however, were not statistically different between the RA and control groups when definitions of hearing loss were considered (unaided pure tone threshold level of ≥25 dB) ( Ahmadzadeh et al., 2017 ).…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Psoriatic arthritis is one of a group of rheumatic diseases called spondyloarthropathies. There are many studies showing that hearing is negatively affected by chronic inflammatory joint diseases other than psoriatic arthritis 14‐16 . In the light of this information, the presence of hearing loss in psoriasis patients with and without joint involvement may be different.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed in patients with psoriatic arthritis 11,12 or patients with psoriasis, including those with psoriatic arthritis 13 . It has been shown that audiovestibular pathology is more common in chronic inflammatory joint diseases 11,12,14‐16 . However, to our knowledge, there is no study evaluating the audiovestibular system of psoriasis patients without joint involvement.…”
Section: Introductionmentioning
confidence: 99%